Effects of anti-money laundering and anti-terrorism financing law on innovation of mobile payment systems in Malaysia - Mhd Sarif, Suhaimi; Maidin, Ainul Jaria; Ibrahim, Jamaludin; Ahmad Dahlan, Abdul Rahman (Emerald Publishing Limited, 2019)
Dynamism of digital economy requires innovation in the mobile payment system to provide for the free flow of information to facilitate electronic transactions. However, regulations and standards were introduced at the global and country levels to impose limitations on mobile payment system to protect consumers’ interests. The Malaysian government introduced the Anti-money Laundering, Anti-terrorism Financing and Proceeds of Unlawful Activities Act 2001 (Act 613) (AMLA) to protect the people from being involved in offences both locally and internationally and an unlawful activity carried out physically or by using virtual mechanisms. It is argued in this study that AMLA has hindered the innovation of the digital economic system that is promoted by the government in line with global developments. The research method adopted is personal interview with selected respondents to gather their views on the challenges posed by the restrictions imposed by AMLA that has had the impact of limiting innovations in the mobile payment system sector.